Economic Evaluation of Pharmacological Treatments in Dementia Disorders - A Systematic Literature Review - Sanjib Saha; Ulf-G. Gerdtham; Håkan Toresson; Lennart Minthon; Johan Jarl (Lund University, School of Economics and Management, Department of Economics, 2018)
The objective is to systematically review the literature on economic evaluations of pharmacological treatments of dementia disorders. A systematic search of published economic evaluation studies in English was conducted using specified key words in relevant databased and websites. Data extracted included methods and empirical evidence (costs, effects, incremental cost-effectiveness ratio) and we assessed if the conclusions made in terms of cost-effectiveness were supported by the reported evidence. The included studies were also assessed for reporting quality using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. Fourteen studies were included in this review. There was a considerable heterogeneity in methodological approaches, use of simulation models, target populations, study time frames, and perspectives as well as comparators used. Keeping these issues in mind, we find that Cholinesterase Inhibitors (ChEIs), and especially donepezil, are dominating no treatment (i.e. less costly and more effective) for mild to moderate AD patients. For moderate to severe AD patients memantine is cost-effective compared to memantine or ChEIs alone. However, the effect of these drugs on survival is yet not established, which could have a major impact on the cost-effectiveness of these drugs. Conclusion: Pharmaceutical treatments are cost-effective comparing to no treatment for dementia patients. However, more research is required on the long-term effectiveness of these drugs, especially on the effects of drugs on survival.
Keywords: H43; I10; I18; 330; Dementia; pharmaceuticals; economic evaluation; Cholinesterase Inhibitors